Experimental studies on the supercooling and melting/freezing characteristics of nano-copper/sodium acetate trihydrate composite phase change materials. (December 2016) - Cui, Wenlong; Yuan, Yanping; Sun, Liangliang; Cao, Xiaoling; Yang, Xiaojiao
Abstract: This paper reports that Nano-copper (Nano-Cu), which possesses high thermal and electrical conductivity, as an additive, can improve the supercooling properties of sodium acetate trihydrate (CH3 COONa·3H2 O, SAT) and enhance its thermal conductivity. To investigate the effect of Nano-Cu content on the degree of supercooling of SAT, composite phase change materials containing SAT, Nano-Cu (0.4%, 0.5%, 0.6%, 0.7% and 0.8%), CMC (thickening agent) and sodium dodecyl sulfonate (C12 H25 NaO3 S, dispersant) were prepared. Melting-freezing experiments involving the composite materials indicated that the rate of heat transfer increased by nearly 20%. When an optimal amount of Nano-Cu (i.e., 0.5%) was added to SAT, the degree of supercooling was reduced to approximately 0.5 °C. Compared to the use of inorganic salt hydrates as nucleating agents, Nano-Cu is significantly advantageous in reducing the degree of supercooling of SAT. The maximum improvement in supercooling was observed when the melting-freezing experiment was conducted at an initial temperature of 70 °C. The thermal conductivity of the reported composite phasechange materialsis approximately 20% higher than that of pure SAT. Highlights: Nano-Cu improves the properties of supercooling and heat transfer of CH3 COONa·3H2 O. The supercooling of CH3 COONa·3H2 O with 0.5% Nano-Cu is approximately 0.5 °C. The thermal conductivity of composite PCM is enhanced by approximately 20%. Nano-Cu can increase the rate of heat transfer by nearly 20%. The composite with Nano-Cu, thickening agent and dispersant has stable performance.